A pharmacopoeial study on the galenical preparations of Datura alba, Nees (Fam. Solanaceae) and Strychnos ignatii, Berg. (Fam. Loganiaceae) - Villarica, Pura R. 1917-
PURPOSE: To prepare pharmacopoeial monographs on Datura alba, Nees and its preparations and to look into the advisability of proposing a pharmacopoeial monograph on Strychnos ignatii, Berg. and its preparations. PROCEDURE: The candidate reviewed thoroughly all the different national pharmacopoeias available in the Philippines as well as all available literature on Datura alba, Nees and Strychnos ignatii Berg. Different lots of various parts of Datura alba, Nees plant, different lots of the seeds of Strychnos ignatii, Berg., and different lots of the tincture of Bolladonna and tincture of Nux vomica obtained from the local drug stores and laboratories were studied and analyzed. Galenical preparations of Datura alba, Nees and Strychnos ignatii, Berg. were made and assayed. From the results of the analyses and assays the monographs of Datura leaf, tincture, fluid extract, and extract of Datura leaf; Datura seed, and tincture of Datura seed were formulated. Approximate amount of time devoted to research are about 16 months. DEGREE OF SUPERVISION: The candidate worked as independently as possible with occasional consultation with the adviser. Several seminars were given by the candidate on the results of her research work. CONTRIBUTION OF RESEARCH TO KNOWLEDGE: Six pharmacopoeial monographs: namely, Datura Leaf, Tincture of Datura Leaf, Fluidextract of Datura Leaf, Extract of Datura Leaf, Datura Seed and Tincture of Datura Seed were presented. As a result of the studies made, no pharmacopoeial monographs for the seeds of Strychnos ignatii, Berg. were proposed because the assay of the seeds of Strychnos nux-vomica grown in the Philippines proved that it is more advantageous to use Nux vomica in lieu of ignatia.
Available to the general public.
Thesis (Master of Science in Pharmacy)--University of the Philippines, 1939.
Keywords: Herbs -- Therapeutic use; Datura; Strychnos